Social Norms and Fundraising: The Trade-Off Between Enhanced Donations and Donor Identity Esteem. Issue 4 (1st October 2016) - Shang, Jen; Sargeant, Adrian
ABSTRACT: The academic literature in fundraising has focused primarily on understanding the drivers for giving. For example, past research shows that the proper use of social information (i.e., perception about the amount of another individual's giving) can increase the amount of a focal donor's contribution by more than 10% without additional fundraising cost. It does so because people use another person's giving to estimate how much on average others give and they then conform to that social norm. This paper examines the degree to which one's perception of a social norm associates not with how much they give but with how good they feel. More specifically, we show that there is a trade-off between how high a perceived social norm is and how good donors feel about themselves. In particular, perceiving others giving at a relatively high level is associated negatively with donors' identity membership esteem. The implications for self-based theory development and the enhancement of fundraising practice are explored.